2022
DOI: 10.3389/fphar.2022.842295
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicines as Effective Reversals of Epithelial-Mesenchymal Transition Induced-Metastasis of Colorectal Cancer: Molecular Targets and Mechanisms

Abstract: Colorectal cancer (CRC) is the third most common type of cancer worldwide. Distant metastasis is the major cause of cancer-related mortality in patients with CRC. Epithelial-mesenchymal transition (EMT) is a critical process triggered during tumor metastasis, which is also the main impetus and the essential access within this duration. Therefore, targeting EMT-related molecular pathways has been considered a novel strategy to explore effective therapeutic agents against metastatic CRC. Traditional Chinese medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 195 publications
0
12
0
Order By: Relevance
“…TCM is an independent factor affecting PFS (11); when combined with chemotherapy and cetuximab or bevacizumab, TCM has been shown to prolong Frontiers in Pharmacology frontiersin.org liver by down-regulating the activation of cancer-associated fibroblasts mediated by CRC-derived ITGBL1-loaded extracellular vesicles (Li et al, 2022); thus, TCM has the unique characteristics of being multi-targeted and multi-linked, and may have a comprehensive therapeutic effect. TCM can also inhibit epithelial-mesenchymal transition by downregulating transforming growth factor-beta, thereby inhibiting invasion and metastasis of CRC cells (Ge et al, 2022), inhibit progression of CRC by suppressing CCL2 and preserving progenitor Tex in an obese microenvironment (Xu et al, 2022) and suppress growth and metastasis of 5-fluorouracil-sensitive/resistant CRC by inhibiting the Wnt singling pathway (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…TCM is an independent factor affecting PFS (11); when combined with chemotherapy and cetuximab or bevacizumab, TCM has been shown to prolong Frontiers in Pharmacology frontiersin.org liver by down-regulating the activation of cancer-associated fibroblasts mediated by CRC-derived ITGBL1-loaded extracellular vesicles (Li et al, 2022); thus, TCM has the unique characteristics of being multi-targeted and multi-linked, and may have a comprehensive therapeutic effect. TCM can also inhibit epithelial-mesenchymal transition by downregulating transforming growth factor-beta, thereby inhibiting invasion and metastasis of CRC cells (Ge et al, 2022), inhibit progression of CRC by suppressing CCL2 and preserving progenitor Tex in an obese microenvironment (Xu et al, 2022) and suppress growth and metastasis of 5-fluorouracil-sensitive/resistant CRC by inhibiting the Wnt singling pathway (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…TCM is effective in the treatment of CRC and can potentially delay cancer recurrence and suppress metastasis ( Ge et al, 2022 ). We previously showed that YQSJ formula in combination with mFOLFOX6 postoperative adjuvant chemotherapy improves the survival rate of advanced CRC patients and decreases the incidence of side effects ( Zhang et al, 2015 ; Zheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional factors that control cell proliferation, survival, and migration are activated when the Wnt protein binds to frizzled family transmembrane receptors, and β-catenin accumulates in the nucleus [ 44 ]. Activation of glycogen synthase kinase 3 (GSK3) is responsible for the effects of curcumin, resveratrol, and EGCG on β-catenin translocation and accumulation in the nucleus [ 43 , 45 , 46 , 47 , 48 ]. Similarly, p53 is responsible for anticancer activity in cells, similar to other signaling pathways.…”
Section: Mechanisms Of Cancer Chemopreventionmentioning
confidence: 99%